Development of an On-Site Protocol to Identify the Adulterations in Palmyrah Jaggery through Comparative Evaluation of Fresh Market samples and Control Sample - Thangavel, Kirushanthi; Thavaputhalvan, Thavapiraja; Chandrajith, Vidana Gayan Gamage; Sivaji, Maathumai; Srivijeindran, Srithayalan (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Palmyrah jaggery, a traditional sweetener valued for its nutritional qualities, is susceptible to adulteration, compromising its authenticity and safety. This study aimed to develop a simple, cost-effective on-site protocol by examining the relationships between sensory attributes, physico-chemical properties, and adulterant test results in market samples compared to a control (QC) sample. Twenty jaggery fresh samples from local producers and a laboratory-prepared QC sample were analyzed. Sensory evaluation assessed the attributes of jaggery such as taste and aroma by Difference From Control method, while physico-chemical parameters, including conductivity, total ash content, moisture content, Brix, pH, and color, were measured using standard methods. Adulterant-specific tests, such as sedimentation, iodine, and saccharin detection, were used to identify impurities like rice bran, starch and CaCO3.The sensory evaluation identified significant differences (p < 0.05) in taste and aroma in 12 samples compared to QC, and 9 tested positive for adulterants like starch and CaCO3. Conductivity and total ash content were reliable indicators of adulteration, as adulterated samples displayed lower values, reflecting reduced mineral content compared to the QC. Moisture content, Brix, pH, and color parameters were less reliable indicators of adulteration due to manufacturing variability, such as processing temperature and filtration methods. Additionally, all market samples exceeded the SLS 521:1981 limit for insoluble matter, suggesting inadequate processing. This study demonstrates the effectiveness of a stepwise detection method combining sensory, physico-chemical, and adulterant-specific tests. The findings provide a foundation for ensuring the authenticity of palmyrah jaggery, promoting sustainable production, consumer safety, and market trust.Palmyrah jaggery, a traditional sweetener valued for its nutritional qualities, is susceptible to adulteration, compromising its authenticity and safety. This study aimed to develop a simple, cost-effective on-site protocol by examining the relationships between sensory attributes, physico-chemical properties, and adulterant test results in market samples compared to a control (QC) sample. Twenty jaggery fresh samples from local producers and a laboratory-prepared QC sample were analyzed. Sensory evaluation assessed the attributes of jaggery such as taste and aroma by Difference From Control method, while physico-chemical parameters, including conductivity, total ash content, moisture content, Brix, pH, and color, were measured using standard methods. Adulterant-specific tests, such as sedimentation, iodine, and saccharin detection, were used to identify impurities like rice bran, starch and CaCO3.The sensory evaluation identified significant differences (p < 0.05) in taste and aroma in 12 samples compared to QC, and 9 tested positive for adulterants like starch and CaCO3. Conductivity and total ash content were reliable indicators of adulteration, as adulterated samples displayed lower values, reflecting reduced mineral content compared to the QC. Moisture content, Brix, pH, and color parameters were less reliable indicators of adulteration due to manufacturing variability, such as processing temperature and filtration methods. Additionally, all market samples exceeded the SLS 521:1981 limit for insoluble matter, suggesting inadequate processing. This study demonstrates the effectiveness of a stepwise detection method combining sensory, physico-chemical, and adulterant-specific tests. The findings provide a foundation for ensuring the authenticity of palmyrah jaggery, promoting sustainable production, consumer safety, and market trust.